Dehydroepiandrosterone Sulfate Deficiencies as Independent Predictors of Increased Coronary Artery Disease in Men with Type II Diabetes Mellitus - Mustafa A-Jabbar Al-Jumaili; Abdullah Ali Mohammed; Hawraa M. Alaa Alden; Sura A. Abdulsattar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The adrenal cortex synthesis the steroid hormone dehydroepiandrosterone (DHEA), has a significant effect on diabetes mellitus. Our study targeted to estimate the relationship between serum levels of DHEA sulphate (DHEAS) and the risk of CAD complication for T2DM in men. Ninety Iraqi male subjects were divided into three groups. Each group has thirty people: thirty people type 2 with diabetes mellitus, thirty person type 2 diabetes mellitus patients with CAD complications, and the control group has thirty healthy people. A significant decrease (p<0.01) of DHEAS, was observed in T2DM with CAD (120.8 µg/dl) compared to both T2DM (141.26 µg/dl) and the control group (239.86 µg/dl). Meanwhile, an increased coronary risk index in T2DM with CAD (10.68) compared to both T2DM (7.56) and control group (4.41) was observed. These findings were confirmed by the negative correlation of DHEAs with coronary risk index. We suggested that a decreased level of DHEAS value may be a beneficial sign for future CAD in patients with T2DM.